Polyurethane resin composition and preparation method thereof
Remove the circular low polymer in the polyethylene methampitenol through the film, and react with the chain expansion and the diocyanate compound to prepare a polyurethane resin composition with a low melting temperature, which solves The problems of mechanical properties and bonding strength have achieved the effects of high flexibility and high adhesion strength.
Patent Information
- Application Number
- CN202380047277.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-07
- Filing Date
- 2023-06-09
- Publication Date
- 2025-01-28
AI Technical Summary
The presence of cyclic oligomers in existing hot melt adhesives leads to deterioration of mechanical properties and bonding strength, and polyurethane resins prepared based on petroleum polyols have shortcomings in low temperature flexibility and hydrolysis resistance.
Perform film distillation by the condition at a temperature from 100 ° C to 250 ° C and a pressure from 100.0 to 1.0. , Prepare a polyurethane resin composition with a low melting temperature.
The effective removal of polyurethane resin composition medium -shaped low polymers, improved the adhesive strength and mechanical properties, while maintaining good flexibility and hydrolysis, suitable for industrial applications of hot -melt adhesives.
Smart Images

Figure BDA0005188303800000101 
Figure BDA0005188303800000141 
Figure BDA0005188303800000151
Abstract
Description
Technical Field
[0001] CROSS REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority based on Korean Patent Application No. 10-2022-0072269 filed on June 14, 2022 and Korean Patent Application No. 10-2023-0073024 filed on June 7, 2023, and all contents described in the related Korean patent applications are incorporated into part of this application.
[0003] The invention relates to a polyurethane resin composition for hot melt adhesive and a preparation method thereof. Background Art
[0004] Generally, articles such as shoes, bags or wallets are configured so that a variety of parts, decorations or fabrics for combination are attached to a main body made of textile or synthetic resin fabric by sewing or bonding. However, when they undergo a sewing process of several steps, a complex suture pattern is formed, and when used for a long time, there is a problem that foreign substances are sandwiched between the sutures, or productivity is reduced by multiple sewing steps during the manufacturing process. Therefore, research on a technology for thermally bonding a variety of decorations or parts in a seamless manner using an adhesive film is being actively conducted.
[0005] Meanwhile, since the adhesive film has a relatively high melting point, it requires a relatively high temperature for thermal bonding. For this reason, there is a problem of causing some damage to the adherend or fabric, and therefore, there is an increasing demand for materials that exhibit adhesive strength even at low temperatures for a short heating time. There is also an increasing demand for adhesives with excellent elongation and elastic recovery for application in areas requiring elasticity.
[0006] Thermoplastic polyurethane resins used as hot melt adhesive films are mainly prepared by reacting high molecular weight diols such as polyester diols or polyether diols with diisocyanates and low molecular weight diols as chain extenders. These thermoplastic polyurethane hot melt adhesives have high tensile strength and elongation at break due to the excellent physical properties of polyurethane resins, and are widely used in clothing due to their good texture and elastic recovery rate.
[0007] Among them, polyether-based polyurethane has relatively low adhesive strength and mechanical properties compared to polyester-based polyurethane but is suitable for use as an adhesive for clothing since it is inexpensive and has excellent flexibility, elongation, and hydrolysis resistance.
[0008] In addition, there is a growing interest in environmentally friendly materials that can reduce the emission of greenhouse gases such as carbon dioxide and obtain carbon credits. As a countermeasure, the polyurethane industry is taking action to reduce the carbon footprint generated during the production process by converting to bio-based raw materials. In fact, plastics with 25% or more bio-based content by weight are given the certification label of "bio-based plastics" to promote industrialization in new product development. Currently commercialized biopolyols can be divided into polyols based on fatty acids using natural fats and oil-based raw materials such as castor oil, and polyols based on polyesters using monomers such as diacids, diols, etc. as raw materials, which are prepared by fermenting using glucose as raw materials. Among them, polyols based on fatty acids have such a disadvantage that the mechanical properties of the prepared polyurethane are reduced, because primary alcohols are mixed with secondary alcohols, resulting in different polarity from existing petroleum-based polyols, which reduces the reactivity with diisocyanates.
[0009] In addition, polyester-based polyols are represented by polytrimethylene succinate prepared by using 1,3-propylene glycol (1,3-PDO) and succinic acid, and when applied to polyurethane, it shows excellent mechanical properties while showing deficiencies in low-temperature flexibility and hydrolysis resistance. In contrast, polytrimethylene ether glycol (PO3G) prepared by using biomass-derived 1,3-PDO as a raw material can provide the most realistic alternative for greenhouse gas reduction without reducing the quality of polyurethane. In this regard, research on its industrial application is continuously being conducted.
[0010] One polymerization method of PO3G is to react 1,3-PDO for a long time under an acid catalyst, however, in the process, a variety of oxidation byproducts and low molecular weight oligomers are simultaneously generated. Among them, cyclic oligomers may bring many side effects to industrial applications. For example, in the case of polytetramethylene ether glycol (PTMG), which is an ether-based polyol, it is known that the cyclic oligomers remaining during film formation cause problems such as deterioration of mechanical properties and blooming phenomenon, in which the cyclic oligomers migrate to the product surface to form white precipitates on the film surface.
[0011] Therefore, research is required to ensure eco-friendliness by industrially applying PO3G prepared from biomaterials to polyurethane resins, and at the same time, ensure quality for replacing polyurethane resins prepared using existing petroleum-based polyols.
[0012] Public Content
[0013] Technical issues
[0014] Provided are a polyurethane resin composition for hot melt adhesive and a preparation method thereof. The polyurethane resin composition uses polytrimethylene ether glycol from which cyclic oligomers are removed.
[0015] Technical Solutions
[0016] To achieve the above object, a polyurethane resin composition is provided, comprising a reaction product of polytrimethylene ether glycol, a chain extender and a diisocyanate, wherein the polytrimethylene ether glycol has a cyclic oligomer content of 0.3 wt % or less.
[0017] Also provided is a method for preparing a polyurethane resin composition, the method comprising: a step of preparing a product containing polytrimethylene ether glycol by polymerizing 1,3-propylene glycol (step 1); a step of removing cyclic oligomers by distilling the product under conditions of a temperature of 100° C. to 250° C. and a pressure of 100.0 torr to 1.0 torr (step 2); a step of preparing a mixture by mixing the product containing polytrimethylene ether glycol from which the cyclic oligomers are removed with a chain extender (step 3); and a step of preparing a polyurethane resin by adding a diisocyanate compound, a catalyst, and a viscosity modifier to the mixture (step 4).
[0018] Hereinafter, the present invention will be described in detail.
[0019] Polyurethane-based adhesives are divided into polyester polyol-based polyurethanes and polyether polyol-based polyurethanes. The adhesive strength of the adhesive is determined by the properties of the adhesive itself and the bonding strength with the adherend. In particular, since the hot melt adhesive has a lower melting temperature, the fluidity becomes better at the bonding temperature, and therefore it has excellent bonding strength with adherends having an uneven structure on the surface, such as fabrics.
[0020] Generally, polyester polyol-based polyurethane adhesives have excellent mechanical strength properties, but have low bonding strength with adherends due to their high melting temperatures, and may have a problem of causing damage to fabrics due to the high bonding temperature.
[0021] The present invention relates to a polyurethane resin composition in which polytrimethylene ether glycol among polyether polyols is used instead of polyester polyols, and since the polyurethane resin composition according to the present invention has a low melting temperature, the above-mentioned problems can be solved. In addition, compared with the existing polytetramethylene glycol, the number of carbon atoms in the repeating unit is small, and thus the elongation of the adhesive is excellent. In addition, it is confirmed that the polytrimethylene ether glycol prepared from biomass raw materials shows excellent adhesive strength and flexibility properties compared with polyester-based biopolyols prepared from other biomass raw materials.
[0022] On the other hand, polytrimethylene ether glycol is obtained by polycondensation of 1,3-propylene glycol (1,3-PDO) and contains a significant level of oligomers in the product. Among the oligomers, cyclic oligomers cause blooming phenomenon when applied to polyurethane-based adhesives, which leads to deterioration of mechanical properties and adhesive strength.
[0023] Therefore, the present invention is characterized in that cyclic oligomers in polytrimethylene ether glycol are selectively removed to reduce the content below a predetermined level, and therefore, even when a polyurethane resin composition is prepared using polytrimethylene ether glycol, adhesive strength and mechanical properties are excellent.
[0024] Preferably, in the polytrimethylene ether glycol, the content of the cyclic oligomer is 0.3 wt% or less, 0.25 wt% or less, 0.2 wt% or less, 0.15 wt% or less, 0.1 wt% or less, 0.09 wt% or less, 0.08 wt% or less, 0.07 wt% or less, 0.06 wt% or less, or 0.05 wt% or less. On the other hand, "cyclic oligomer" refers to a substance having a cyclic chemical structure in which 1,3-PDO loses its functional group by intramolecular reaction during polycondensation, and in particular, in the present invention, it refers to highly volatile dimers to pentamers (2 monomers to 5 monomers are polymerized), which cause problems in the use of the product. In addition, the theoretical lower limit of the content of cyclic oligomers in polytrimethylene ether glycol is 0 wt %, but it may be, for example, 0.001 wt % or more, 0.002 wt % or more, 0.003 wt % or more, 0.004 wt % or more, or 0.005 wt % or more.
[0025] Preferably, the molecular weight distribution of the polytrimethylene ether glycol is 1.0 or more, 1.1 or more, 1.2 or more, 1.3 or more, 1.4 or more, or 1.5 or more; and 3.0 or less, 2.9 or less, 2.8 or less, 2.7 or less, 2.6 or less, or 2.5 or less. As described below, the above molecular weight distribution is not significantly reduced in the molecular weight distribution of the polytrimethylene ether glycol prepared from 1,3-PDO. In other words, this means that in the polytrimethylene ether glycol according to the present invention, only the components that affect the physical properties of the polytrimethylene ether glycol are effectively removed.
[0026] Preferably, in polytrimethylene ether glycol, the content of 1,3-propylene glycol is 0.1wt% or less. More preferably, the content of 1,3-propylene glycol in the polytrimethylene ether glycol according to the present invention is 0.09wt% or less, 0.08wt% or less, 0.07wt% or less, 0.06wt% or less, or 0.05wt% or less. In addition, the theoretical lower limit of the content of 1,3-propylene glycol in polytrimethylene ether glycol is 0wt%, but it can be, for example, 0.001wt% or more, 0.002wt% or more, 0.003wt% or more, 0.004wt% or more, or 0.005wt% or more.
[0027] Preferably, the number average molecular weight of the polytrimethylene ether glycol is 500 to 4,000. More preferably, the number average molecular weight of the polytrimethylene ether glycol according to the present invention is 600 or more, 700 or more, 800 or more, 900 or more, or 1,000 or more; and 3,800 or less, 3,600 or less, 3,400 or less, 3,200 or less, or 3,000 or less.
[0028] Preferably, the chain extender includes one or more selected from the group consisting of ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 2-methylpentanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol and neopentyl glycol. More preferably, the chain extender is 1,6-hexanediol.
[0029] The diisocyanate may be exemplified by aromatic isocyanates, aliphatic diisocyanates or alicyclic diisocyanates. Preferably, the diisocyanate may be selected from the group consisting of naphthalene diisocyanate, diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), tolidine diisocyanate (TODI), p-phenylene diisocyanate (PPDI), hexamethylene diisocyanate (HDI), dicyclohexylmethane diisocyanate (H12MDI), isophorone diisocyanate (IPDI) and a mixture of two or more thereof.
[0030] Preferably, 50 to 89 parts by weight of polytrimethylene ether glycol, 1 to 10 parts by weight of a chain extender, and 10 to 40 parts by weight of a diisocyanate compound may be included. More preferably, polytrimethylene ether glycol may be included in an amount of 51 parts by weight or more, 52 parts by weight or more, 53 parts by weight or more, 54 parts by weight or more, or 55 parts by weight or more; and 85 parts by weight or less, 84 parts by weight or less, 83 parts by weight or less, 82 parts by weight or less, 81 parts by weight or less, or 80 parts by weight or less. In addition, more preferably, the chain extender may be included in an amount of 2 parts by weight or more, 3 parts by weight or more, or 3.5 parts by weight or more; and 9 parts by weight or less, 8 parts by weight or less, or 7.5 parts by weight or less. In addition, more preferably, the diisocyanate compound may be contained in an amount of 12 parts by weight or more, 13 parts by weight or more, 15 parts by weight or more, or 17 parts by weight or more; and 38 parts by weight or less, 36 parts by weight or less, 35 parts by weight or less, or 33 parts by weight or less.
[0031] Preferably, the above polyurethane resin composition may have a biocontent of 25 wt% or more, more preferably 30 wt% or more, 35 wt% or more, 40 wt% or more, 45 wt% or more, or 50 wt% or more. The polyurethane resin composition may be prepared from polytrimethylene ether glycol prepared by polymerizing biomass-derived 1,3-propylene glycol, and the biocontent means the content of carbon based on biological raw materials in the total carbon content of the polyurethane resin composition.
[0032] In addition, the present invention provides an adhesive film comprising the polyurethane resin composition.
[0033] Furthermore, the present invention provides a hot melt adhesive comprising an adhesive film.
[0034] In addition, the present invention provides a method for preparing the above polyurethane resin composition, the method comprising the following steps:
[0035] preparing a product comprising polytrimethylene ether glycol by polymerizing 1,3-propylene glycol (step 1);
[0036] removing cyclic oligomers by distilling the product at a temperature of 100° C. to 250° C. and a pressure of 100.0 torr to 1.0 torr (step 2);
[0037] preparing a mixture by mixing a product including polytrimethylene ether glycol from which cyclic oligomers are removed with a chain extender (step 3); and
[0038] A polyurethane resin is prepared by adding a diisocyanate compound, a catalyst, and a viscosity modifier to the mixture (step 4).
[0039] Hereinafter, each step of the present invention will be described in detail.
[0040] Step 1
[0041] Step 1 of the present invention is a step of preparing a product including polytrimethylene ether glycol by polymerizing 1,3-propylene glycol.
[0042] As long as Step 1 is a reaction for preparing polytrimethylene ether glycol from 1,3-propylene glycol, there is no particular limitation on the reaction conditions, and polytrimethylene ether glycol is preferably prepared by polycondensing 1,3-propylene glycol using a polycondensation catalyst.
[0043] Specifically, as polycondensation catalyst, catalyst is selected from the group consisting of Lewis acid, Bronsted acid, superacid and mixture thereof. More preferably, catalyst is selected from the group consisting of inorganic acid, organic sulfonic acid, heteropolyacid and metal salt. Most preferably, catalyst is selected from the group consisting of sulfuric acid, fluorosulfonic acid, phosphoric acid, p-toluenesulfonic acid, benzenesulfonic acid, phosphotungstic acid, phosphomolybdic acid, trifluoromethanesulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, 1,1,1,2,3,3-hexafluoropropanesulfonic acid, bismuth trifluoromethanesulfonate, yttrium trifluoromethanesulfonate, ytterbium trifluoromethanesulfonate, neodymium trifluoromethanesulfonate, lanthanum trifluoromethanesulfonate, scandium trifluoromethanesulfonate and zirconium trifluoromethanesulfonate. Catalyst is also selected from the group consisting of zeolite, fluorinated alumina, acid-treated silica, acid-treated silica-alumina, heteropolyacid and heteropolyacid supported on zirconium oxide, titanium dioxide, alumina and / or silica. More preferably, sulfuric acid is used as polycondensation catalyst.
[0044] The catalyst is preferably used in a concentration of 0.1 wt% to 20 wt%, more preferably 1 wt% to 5 wt%, based on the weight of the reaction mixture.
[0045] In addition, the polycondensation is preferably performed at 150° C. to 250° C., more preferably 160° C. to 220° C. In addition, the reaction is preferably performed in the presence of an inert gas, preferably under nitrogen.
[0046] In addition, after the polycondensation, a hydrolysis reaction may be further performed to remove the acid bound to the polytrimethylene ether glycol. In addition, a neutralization reaction may be further performed after the hydrolysis reaction.
[0047] Step 2
[0048] Step 2 is a step of removing cyclic oligomers, 1,3-PDO and oxidation byproducts by distilling the product of step 1. To this end, the thin film distillation of step 2 is performed under the conditions of a temperature of 100° C. to 250° C. and a pressure of 100.0 Torr to 1.0 Torr.
[0049] On the other hand, as used herein, the term "thin film distillation" refers to a distillation method in which the mixture to be separated is prepared into a thin film to increase the surface area in contact with the heat source. For example, the mixture introduced into the thin film distiller forms a thin film on the inner wall of the thin film distiller by physical force (e.g., a wiper), and is distilled by applying an appropriate temperature via a heat source (e.g., a heating medium), so thin film distillation is possible. In addition, when the pressure in the thin film distiller decreases, the vapor pressure of the material decreases, and therefore there is an advantage that evaporation occurs at a temperature lower than the original boiling point. In addition, a condenser for recovering the evaporated material, i.e., the material to be removed, can be provided inside the thin film distiller.
[0050] In addition, thin film distillation has the advantage that the mixture to be separated can be applied continuously. For example, thin film distillation can be continuously performed by continuously introducing the mixture to be separated into the upper part of the distiller and recovering the purified mixture from the lower part of the distiller.
[0051] The thin film distillation of step 2 is performed at a temperature of 100° C. to 250° C., preferably 110° C. or higher, 120° C. or higher, 130° C. or higher, 140° C. or higher, or 150° C. or higher; 240° C. or lower, 230° C. or lower, 220° C. or lower, 210° C. or lower, or 200° C. or lower. When the temperature is lower than 100° C., the effect of distillation is weak and it is difficult to remove the substance to be removed, and when the temperature is higher than 250° C., there is a concern about thermal oxidation of polytrimethylene ether glycol.
[0052] The thin film distillation of step 2 is carried out at a pressure of 100.0 torr to 1.0 torr, preferably 90.0 torr or less, 80.0 torr or less, 70.0 torr or less, 60.0 torr or less, or 50.0 torr or less, and 5.0 torr or more, 6 torr or more, 7 torr or more, 8 torr or more, 9 torr or more, or 10.0 torr or more. When the pressure is higher than 100.0 torr, there is a problem of reduced separation efficiency, and when the pressure is lower than 1.0 torr, there is a problem of too high separation efficiency, and thus the components that should remain in the product are separated, resulting in a lower yield of the final product.
[0053] At the same time, the volatilized components, ie, the substances to be removed in the thin film distiller, can be discharged to the lower part of the thin film distiller through the condenser, whereby the remaining purified mixture, ie, the distillation residue, can be recovered separately.
[0054] Step 3
[0055] Step 3 of the present invention is a step of preparing a mixture by mixing a product including polytrimethylene ether glycol from which cyclic oligomers are removed with a chain extender.
[0056] The content of cyclic oligomers in polytrimethylene ether glycol and the chain extender are as described above.
[0057] The method of mixing polytrimethylene ether glycol with the chain extender is not particularly limited, and the materials may generally be injected into a stirrer and then mixed. At this time, it is preferred to maintain the temperature at about 60° C. to about 90° C. or about 65° C. to 85° C. so that the mixture can maintain a liquid phase.
[0058] Step 4
[0059] Step 4 of the present invention is a step of preparing a polyurethane resin by adding a diisocyanate compound, a catalyst and a viscosity modifier to a mixture of polytrimethylene ether glycol and a chain extender.
[0060] The specific type of the diisocyanate compound is as described above, and (the number of moles of NCO functional groups in the diisocyanate compound / the number of moles of OH functional groups in the polyol compound and the chain extender) is preferably about 0.8 to about 1.2, about 0.9 to about 1.1, or about 0.95 to about 1.05.
[0061] As the catalyst, a bismuth-based catalyst may be used. As the bismuth-based catalyst, for example, a catalyst containing a bismuth compound such as bismuth octoate, bismuth naphthenate, bismuth propionate, bismuth neodecanoate, bismuth trineodecanoate, etc. may be used.
[0062] In addition, in order to promote the reactivity or processability of the prepared product, a viscosity modifier may be additionally added, and dimethylformamide (DMF) is preferably used as the viscosity modifier. When the viscosity reaches the target value by continuing the reaction after adding the viscosity modifier, a reaction terminator is added and the product is cooled to obtain a polyurethane resin composition. As the reaction terminator, alcohols are used, for example, ethanol may be used.
[0063] Effects of the Invention
[0064] As described above, the present invention can provide a polyurethane resin for a hot melt adhesive suitable for clothing by removing cyclic oligomers in polytrimethylene ether glycol and a preparation method thereof.
[0065] Detailed description of implementation plan
[0066] Hereinafter, in order to better understand the present invention, preferred exemplary embodiments will be provided. However, the following exemplary embodiments are provided only to illustrate the present invention, and the scope of the present invention is not limited thereto.
[0067] In the following Preparation Examples, Examples, and Comparative Examples, each physical property was measured as follows.
[0068] 1) Molecular weight distribution (Mw / Mn) and total content (wt%) of oligomers
[0069] The polytrimethylene ether glycol prepared in each of the following preparation examples was dissolved in tetrahydrofuran (THF) at a concentration of 1 wt %, and gel permeation chromatography (manufacturer: WATERS, model: Alliance, detector: 2414RI detector, column: Strygel HR 0.5 / 1 / 4) was used, and polyethylene glycol was used as a standard material to calculate the weight average molecular weight (Mw) and number average molecular weight (Mn), respectively. Based on the measured Mw and Mn, the molecular weight distribution value and the content of low molecular weight oligomers having an Mn of 400 or less were calculated.
[0070] 2) 1,3-PDO content (wt%) and cyclic oligomer content (wt%)
[0071] 0.5 g of polytrimethylene ether glycol prepared in each of the following preparation examples was dissolved in 10 mL of methanol, followed by measurement using gas chromatography (model: agilent 7890, column: DBWAX), and 1 g of each reference material was dissolved in 10 mL of methanol. After further dilution according to the concentration and measurement using a standard reference, the content (wt%) of 1,3-PDO and the content (wt%) of cyclic oligomers contained in the polytrimethylene ether glycol were calculated.
[0072] 3) OHV
[0073] 6 g of polytrimethylene ether glycol prepared in each of the following preparation examples and 15 mL of an acetylation agent (acetic anhydride / pyridine=10 / 40 vol%) were injected into a 100 mL flask and allowed to react for 30 minutes at 100° C. under a reflux atmosphere. After the reaction, cooling to room temperature was performed, and then 50 mL of distilled water was injected. The reactant prepared above was titrated with 0.5 N KOH using an automatic titrator (manufacturer: metrohm, Titrino 716), and OHV was calculated according to the following mathematical equation 1.
[0074] [Mathematical equation 1]
[0075] OHV = 56.11 × 0.5 × (AB) / sample feed amount
[0076] In mathematical equation 1,
[0077] 56.11 represents the molecular weight of KOH,
[0078] 0.5 represents the normal concentration of KOH.
[0079] A represents the dispensed amount of KOH solution used in the blank test, and
[0080] B represents the injection amount of the KOH solution used in the sample titration.
[0081] The measured OHV was converted into an end group average molecular weight (Mn) according to the following mathematical equation 2.
[0082] [Mathematical equation 2]
[0083] Mn=(56.11×2 / OHV)×1000
[0084] Preparation Example 1: Preparation of polyols
[0085] 1) Preparation of polyol A
[0086] Step a)
[0087] Biomass-derived 1,3-propanediol (15 kg) and sulfuric acid (150 g) were charged into a 20 L glass double-jacketed reactor equipped with a sparger and a stirrer made of Teflon, and then a polymer was prepared at 166° C. for 16 hours under nitrogen sparging, and reaction byproducts were removed through an upper condenser.
[0088] Step b)
[0089] Then, deionized water (5 kg) was added, and the resulting mixture was maintained at 95° C. for 4 hours under nitrogen purge to hydrolyze the acid esters formed during the polymerization. After the hydrolysis, 170 g of soda ash in 1000 mL of deionized water was added, and the mixture was heated to 80° C. while stirring under a nitrogen stream. Neutralization was continued for 1 hour, and then the product was dried at 120° C. under reduced pressure and filtered using a Nutche filter to obtain a polytrimethylene ether glycol product.
[0090] 2) Preparation of polyol B
[0091] A polytrimethylene ether glycol product was obtained in the same manner as in the preparation method of polyol A, except that the reaction time in step a) was changed from 16 hours to 26 hours.
[0092] The physical properties of the polyol A and polyol B prepared above are shown in Table 1 below.
[0093] [Table 1]
[0094]
[0095] Preparation Example 2: Removal of cyclic oligomers by thin film distillation
[0096] Each of the polyols prepared in the Preparative Examples was purified using a laboratory-scale thin-film distillation apparatus.
[0097] In detail, the thin film distillation apparatus was VTA's VKL-70-4 model, and was a short path distillation type in which a condenser was installed inside a distillation column and had an evaporation diameter of 70 mm and a flow rate of 0.04 m. 2 When the distillation column jacket is set to a suitable temperature by the hot oil system and the interior of the column reaches a target vacuum level due to the vacuum pump, each sample prepared previously is introduced into the upper part of the distillation column at a suitable feed rate. At this time, polytrimethylene ether glycol forms a film having a uniform thickness inside the column by a mechanical stirrer equipped with a scraper, and evaporated low molecular weight materials are condensed in an internal condenser and discharged as a distillate, and purified polytrimethylene ether glycol is discharged as a residue.
[0098] Each of the prepared polyols was tested at a feed rate of 1 kg / h for 1 hour, and after the test, sampling was performed to measure physical properties, and the results are shown in Table 2 below.
[0099] [Table 2]
[0100] unit Polyol C Polyol D Feed polyol Polyol A Polyol B Feed rate kg / h 1 1 Evaporation temperature ℃ 150 180 Internal condenser temperature ℃ 50 50 Vacuum level Trust 20 10 Distillate wt% 0.4 0.3 Residue wt% 99.6 99.7 OHV - 117.86 58.74 Average Mn of terminal group g / mol 952 1910 Polydispersity - 1.5 2.2 Cyclic oligomer content wt% 0.03 0.02 1,3-PDO content wt% 0.05 0.04 Linear dimer content wt% 0.22 0.09
[0101] Example 1
[0102] 61.78% by weight (50 mol%) of polytrimethylene ether glycol (PO3G1000, polyol C) having a molecular weight of 1000 subjected to thin film distillation and 7.30% by weight (50 mol%) of 1,6-hexanediol were injected into a stirrer and mixed by stirring at a temperature of 80°C at which the composition maintained a liquid phase. 30.92% by weight of MDI (100 mol% / OH:NCO=1:1) and bismuth trineodecanoate (300 ppm) as a catalyst were gradually added thereto to prevent heat generation. In order to control the viscosity, dimethylformamide (DMF) was added to continue the reaction, and when the viscosity reached the target value, ethanol was added as a reaction terminator, and cooled to below 40°C to prepare a thermoplastic polyurethane resin. After bar coating, the prepared resin was dried at 80°C in a hot air dryer for 12 hours to produce an adhesive film having a thickness of 30 μm to 100 μm.
[0103] Example 2
[0104] A polyurethane resin and an adhesive film were prepared in the same manner as in Example 1, except that the feed amounts were changed as follows: 76.37% by weight (50 mol%) of polytrimethylene ether glycol (PO3G2000, Polyol D) having a molecular weight of 2000 subjected to thin film distillation, 4.51% by weight (50 mol%) of 1,6-hexanediol and 19.11% by weight of MDI (100 mol% / OH:NCO=1:1).
[0105] Comparative Example 1
[0106] A polyurethane resin and an adhesive film were prepared in the same manner as in Example 1, except that the feed amounts were changed as follows: 61.78% by weight (50 mol%) of polytrimethylene ether glycol (PO3G1000, Polyol A) having a molecular weight of 1000, 7.30% by weight (50 mol%) of 1,6-hexanediol, and 30.92% by weight of MDI (100 mol% / OH:NCO=1:1).
[0107] Comparative Example 2
[0108] A polyurethane resin and an adhesive film were prepared in the same manner as in Example 1, except that the feed amounts were changed as follows: 76.37% (50 mol%) by weight of polytrimethylene ether glycol (PO3G2000, Polyol B) having a molecular weight of 2000, 4.51% (50 mol%) by weight of 1,6-hexanediol, and 19.11% by weight of MDI (100 mol% / OH:NCO=1:1).
[0109] Comparative Example 3
[0110] A polyurethane resin and an adhesive film were prepared in the same manner as in Example 1, except that the feed amounts were changed as follows: 61.78% by weight (50 mol%) of polytetramethylene ether glycol (PTMG1000) having a molecular weight of 1000, 7.30% by weight (50 mol%) of 1,6-hexanediol, and 30.92% by weight of MDI (100 mol% / OH:NCO=1:1).
[0111] Comparative Example 4
[0112] A polyurethane resin and an adhesive film were prepared in the same manner as in Example 1, except that the feed amounts were changed as follows: 76.37% by weight (50 mol%) of polytetramethylene ether glycol (PTMG2000) having a molecular weight of 2000, 4.51% by weight (50 mol%) of 1,6-hexanediol, and 19.11% by weight of MDI (100 mol% / OH:NCO=1:1).
[0113] Comparative Example 5
[0114] A polyurethane resin and an adhesive film were prepared in the same manner as in Example 1, except that the feed amounts were changed as follows: 61.78% by weight (50 mol%) of poly(succinic acid / 1,3-PDO) having a molecular weight of 1000, 7.30% by weight (50 mol%) of 1,6-hexanediol, and 30.92% by weight of MDI (100 mol% / OH:NCO=1:1).
[0115] Comparative Example 6
[0116] A polyurethane resin and an adhesive film were prepared in the same manner as in Example 1, except that the feed amounts were changed as follows: 76.37% by weight (50 mol%) of poly(succinic acid / 1,3-PDO) having a molecular weight of 2000, 4.51% by weight (50 mol%) of 1,6-hexanediol, and 19.11% by weight of MDI (100 mol% / OH:NCO=1:1).
[0117] Comparative Example 7
[0118] A polyurethane resin and an adhesive film were prepared in the same manner as in Example 1, except that the feed amounts were changed as follows: 61.78% by weight (50 mol%) of polybutylene adipate diol (PBA-1000) having a molecular weight of 1000, 7.30% by weight (50 mol%) of 1,6-hexanediol, and 30.92% by weight of MDI (100 mol% / OH:NCO=1:1).
[0119] Comparative Example 8
[0120] A polyurethane resin and an adhesive film were prepared in the same manner as in Example 1, except that the feed amounts were changed as follows: 76.37% by weight (50 mol%) of polybutylene adipate diol (PBA-2000) having a molecular weight of 2000, 4.51% by weight (50 mol%) of 1,6-hexanediol, and 19.11% by weight of MDI (100 mol% / OH:NCO=1:1).
[0121] Experimental Examples
[0122] The physical properties of the polyurethane resins or adhesive films prepared in Examples and Comparative Examples were evaluated as follows, and the results are shown in Tables 3 and 4 below.
[0123] 1) Tensile strength, elongation, 100% modulus, 300% modulus and elasticity
[0124] Tensile strength and elongation, 100% modulus and 300% modulus were measured using a universal testing machine (model: Instron 4465, manufacturer: Instron) according to ASTM D412 (a specimen having a width of 20 mm, a length of 100 mm and a thickness of 50 μm, a tensile rate of 500 mm / min).
[0125] 2) Koefler melting point
[0126] Koefler melting point was measured using a Koefler hot bench (Karg Industrietechnik, Germany). In detail, a film having a thickness of 50 μm x a width of 1 cm x a length of 20 cm was placed on a 30 cm long metal plate having a temperature gradient from room temperature to 230° C. for 30 seconds, and then the temperature of the metal plate at the portion of the film broken by lifting was expressed as a melting point (the temperature of the metal plate was measured using six materials having a melting point between 69.7° C. for stearic acid and 226.5° C. for saccharin).
[0127] 3) Biocontent (wt%)
[0128] The bio-based carbon content of the Preparation Examples was measured among the total carbon content of the polyurethane resins prepared in the Examples and Comparative Examples.
[0129] 4) Adhesion strength
[0130] TPU fabric (VENTWIN, ), the adhesive films prepared in the examples and comparative examples, and a waterproof polyester fabric (Sewing House, ANS-217) were bonded in a heat press at 140°C for 20 seconds in this order, and the bonding strength was measured using a universal testing machine (500N load cell) according to the method specified in ASTM D 1876 (the width of the bonded part was 25 mm and the tensile speed was 10 inches / minute).
[0131] [Table 3]
[0132]
[0133] As shown in Table 3, the polyurethane adhesive films (Comparative Examples 1 and 2) containing polytrimethylene ether glycol in which cyclic oligomers remain have a blooming phenomenon in which the oligomers migrate to the surface, resulting in deterioration of the physical properties and adhesive strength of the adhesive film. In contrast, it was confirmed that the polyurethane adhesive films according to the present invention (Examples 1 and 2) manufactured using polytrimethylene ether glycol containing a predetermined level or less of cyclic oligomers have no blooming phenomenon and show improvements in both flexibility and adhesive strength.
[0134] [Table 4]
[0135]
[0136] In Table 4, it was confirmed that Comparative Examples 3, 4, 7 and 8, which are polyurethane resin adhesive films containing existing petroleum-based polyols, showed excellent adhesive strength when using polyester polyols compared to polyether polyols, but showed low flexibility, and therefore, they have limitations in adhesives for clothing with frequent deformation. It was also confirmed that the melting point of the polyurethane adhesive tends to be quite high due to the characteristics of polyester bonding, which may cause damage to the fabric to be bonded.
[0137] It was confirmed that Examples 1 and 2 according to the present invention had excellent flexibility properties due to high elongation values, while showing bonding strengths comparable to those of Comparative Examples 7 and 8 containing petroleum-based polyester polyols, and had both excellent elongation and bonding strength compared to the case of using biopolyester polyols (as in Comparative Examples 4 and 5).
Claims
1. A polyurethane resin composition comprising a reaction product of polytrimethylene ether glycol, a chain extender and a diisocyanate, wherein the polytrimethylene ether glycol has a cyclic oligomer content of 0.3 wt % or less. 2 . The polyurethane resin composition according to claim 1 , wherein the polytrimethylene ether glycol has a cyclic oligomer content of 0.05 wt % or less. 3 . The polyurethane resin composition according to claim 1 , wherein the polytrimethylene ether glycol has a molecular weight distribution (Mw / Mn) of 1.0 to 3.
0. 4 . The polyurethane resin composition according to claim 1 , wherein the polytrimethylene ether glycol has a 1,3-propylene glycol content of 0.1 wt % or less. The polyurethane resin composition according to claim 1 , wherein the polytrimethylene ether glycol has a number average molecular weight of 500 to 4,000.
6. The polyurethane resin composition according to claim 1, wherein the chain extender comprises one or more selected from the group consisting of ethylene glycol, diethylene glycol, propylene glycol, dipropylene glycol, 1,3-butanediol, 1,4-butanediol, 2-methylpentanediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanediol, 1,4-cyclohexanedimethanol, 3-methyl-1,5-pentanediol and neopentyl glycol.
7. The polyurethane resin composition according to claim 1, wherein the diisocyanate is selected from the group consisting of naphthalene diisocyanate, diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), tolidine diisocyanate (TODI), p-phenylene diisocyanate (PPDI), hexamethylene diisocyanate (HDI), dicyclohexylmethane diisocyanate (H12MDI), isophorone diisocyanate (IPDI) and a mixture of two or more thereof. 8 . The polyurethane resin composition according to claim 1 , comprising 50 to 89 parts by weight of the polytrimethylene ether glycol, 1 to 10 parts by weight of the chain extender, and 10 to 40 parts by weight of the diisocyanate compound.
9. The polyurethane resin composition according to claim 1, wherein the bio-content is 25 wt% or more. 10 . An adhesive film comprising the polyurethane resin composition according to claim 1 . 11 . A hot melt adhesive comprising the adhesive film according to claim 10 .
12. A method for preparing a polyurethane resin composition according to any one of claims 1 to 7, the method comprising the following steps: preparing a product comprising polytrimethylene ether glycol by polymerizing 1,3-propylene glycol (step 1); removing cyclic oligomers by distilling the product at a temperature of 100° C. to 250° C. and a pressure of 100.0 torr to 1.0 torr (step 2); preparing a mixture by mixing a product including polytrimethylene ether glycol from which cyclic oligomers are removed with a chain extender (step 3); and The polyurethane resin is prepared by adding a diisocyanate compound, a catalyst, and a viscosity modifier to the mixture (step 4).
13. The method according to claim 12, wherein the temperature of step 2 is 150°C to 200°C.
14. The method according to claim 12, wherein the pressure of step 2 is 50.0 Torr to 1.0 Torr.
Citation Information
Patent Citations
Future car headlamp cover lens vision inspection device
KR1020220072269A
Auto infusion solution injector
KR1020230073024A